2-Oxo-2H-chromen-3-yl 4-fluorobenzoate - Eric Ziki; Siaka Sosso; Lamine Cissé; Guy Euloge Bany; Abdoulaye Djandé; Rita Kakou-Yao (IUCrData, 2017)
In the title compound, C16H9FO4, the dihedral angle between the planar coumarin ring system [maximum deviation = 0.027 (1) Å] and the benzene ring is 70.18 (6)°. In the crystal, π–π interactions [shortest centroid–centroid separation = 3.5338 (8) Å] link the molecules into a three-dimensional framework.